The globalization of regional clusters : between localization and internationalization - Fornahl, Dirk; Grashof, Nils (New horizons in regional science series, 2021)
"Addressing the role of regional clusters in the context of ongoing globalization, this timely book investigates the two seemingly competing trends of globalization and localization from both quantitative and qualitative perspectives. International case studies offer pioneering insights into the internationalization process of regional clusters and the effect of this on regional as well as firm performance. Chapters discuss the link between localization in a regional cluster in a transition economy and firms' internationalization, the internal/external relationships of clusters and radical innovations, and internationally organized resilience capacities of industries and regional clusters. The book highlights the role of clusters in wider networks including global value chains and the specific role of migrants in the internationalization patterns of regional clusters. Innovative and forward-looking, this book will be a helpful read for scholars and students of economic geography and innovation. The critical case studies examined will also help public policy and regional policy makers"--